Pattern and Determinants of Birth Weight in a Rural Popula-tion of Punjab, India - Mahesh Satija; Vikram Kumar Gupta; Anurag Chaudhary; Sarit Sharma; Sangeeta Girdhar; Surinderpal Singh (Medsci Publications, 2017)
Introduction: Birth weight is a strong predictor for ensuring healthy life of a newborn and is affected by various maternal and social determinants. The study was planned to analyze the pattern of birth weight of newborns and to identify possible factors affecting birth weight. Materials and Methods: A community based retrospective cohort study was conducted by identifying a birth cohort of 332 live born between 1st January 2014 to 31st December, 2014 under Rural Health Training Centre, Department of Community Medicine, Dayanand Medical College & Hospital, Ludhiana, Punjab. Data on birth weight and socio-demographic characteristics was collected from the records maintained at the centre by health workers through regular house to house visits. Results: Mean birth weight was 2.69±0.57kg. Lower mean birth weight was significantly associated with younger maternal age, lower socio-economic status, lower maternal height and pre-pregnancy underweight mothers. The incidence of low birth weight (<2.5 kg) was 18.1%. Among all live births, 23.8% were delivered prior to 37 weeks of gestation (preterm). Multiple regression analysis identified younger maternal age, low maternal height and underweight mothers as significant determinants associated with lower mean birth weight. Conclusion: The study identifies certain determinants for lower birth weight for which appropriate interventions need to be planned to ensure a healthy ageing.